Correlation between stress hyperglycemia ratio and prognosis in acute myocardial infarction patients following percutaneous coronary intervention - Wei Meng; Hui Qiu; Weiping Li; Weiping Li; Weiping Li; Hongwei Li; Hongwei Li; Hongwei Li (Frontiers in Cardiovascular Medicine)
BackgroundStress hyperglycemia ratio (SHR) is a commonly used predictor of acute hyperglycemia. The present study aimed to evaluate the prognostic significance of SHR in acute myocardial infarction (AMI) patients who underwent percutaneous coronary intervention (PCI).MethodsA total of 3,212 consecutive AMI patients who underwent PCI were recruited and assigned to three groups, according to SHR tertiles. Then, the total number of major adverse cardiovascular and cerebrovascular events (MACCEs) and various cardiovascular events were recorded. The SHR was determined, as follows: admission blood glucose (mmol/L)/[1.59 × hemoglobin A1c (%) −2.59].ResultsThe incidence of MACCEs was positively correlated to SHR during the median follow-up of 36 months. The multivariate COX regression analysis identified SHR as an independent predictor of composite MACCEs [hazard ratio: 2.279, 95% confidence interval (CI): 1.569–3.311, p < 0.001] and target vessel revascularization (hazard ratio: 1.998, 95% CI: 1.299–3.074, p = 0.002). In terms of gender, age, type of AMI, body mass index, left ventricular ejection fraction, and diabetes mellitus, SHR >1.45 was significantly associated to MACCEs across all subgroups (all, p < 0.001), except for patients with ejection fraction <50%. Furthermore, the area under the receiver operating characteristic curve for SHR in predicting MACCEs was 0.636 (95% CI: 0.613–0.659, p < 0.05), with a cut-off value of 1.317.ConclusionsStress hyperglycemia, as indicated by SHR, is significantly correlated to MACCEs, and independently predicts the prognosis of AMI patients undergoing PCI. These findings highlight the potential of SHR as an effective prognostic marker for AMI patients undergoing PCI.